“Online Cosmetic Shopping Trends Among Women: A Demographic And Empirical Analysis In Gujarat” - Badgujar, Ms. Uma; Sinha, Dr. Kunjal (Metallurgical and Materials Engineering, 2025)
The impact of the proliferation of e-commerce on the purchasing behaviour of female consumers regarding cosmetics in Gujarat, India. The quantitative study is demonstrating different demographical factors which impact on utilization of internet for cosmetics shopping among women. Data on the perspectives was collected from 500 female respondents from various age categories, economic classes, and employment statuses through a structured questionnaire and statistical analysis. This study explores how much brand awareness, brand loyalty, and brand association influence online buying behavior and purchase decisions. Data shows that demographic factors including age, income, and education significantly influence consumer choices and online purchasing behaviors. Insights of findings enhance the understanding of consumers’ decision-making process in the context of the digital marketplace and guide strategies for e-commerce platforms and businesses in the cosmetics industry.